A preliminary account of Culicoides (Diptera: Ceratopogonidae) from the Andaman and Nicobar Islands with 13 new records and updated species inventory from India - Koustav Mukherjee; Surajit Kar; Atanu Naskar; Chandrakasan Sivaperuman; Dhriti Banerjee (Parasites & Vectors)
Abstract Background The detection of multiple bluetongue virus serotypes, increasing trend in livestock density, rich biological diversity with high endemism, and the status of the Andaman and Nicobar Islands as a popular tourist destination underscore the need for a faunistic survey of medically and veterinary significant vector species, specifically Culicoides, in this region. Moreover, scattered information on Indian Culicoides species complicates the planning and implementation of preventive measures for pathogens transmitted by these vectors. This study aims to provide the first comprehensive account of the Culicoides fauna in the Andaman and Nicobar Islands, India, along with an updated checklist of Indian Culicoides species and their state-wise distribution. Methods Surveys were conducted across various habitats in the Andaman and Nicobar Islands in September 2022 and 2023. Midges were collected using CDC light traps, light sheets, Malaise traps, and manual collection from exposed body parts of the author and volunteers (biting collection). Identification was carried out using relevant taxonomic keys and original descriptions. Additionally, an updated checklist of Indian Culicoides, based on published and grey literature from 1910 to the present, is provided, with an emphasis on their potential role in pathogen transmission. Results A total of 3529 adult Culicoides were trapped during the survey, representing 5 subgenera and 3 unplaced species groups. The study recorded 23 Culicoides species, including 13 new species records for India: C. barnetti, C. gouldi, C. flaviscutellaris, C. flavipunctatus, C. hui, C. histrio, C. guttifer, C. perornatus, C. okinawensis, C. quatei, C. obscurus, C. coronalis, and C. kusaiensis. Conclusions The Indian Culicoides fauna now includes 93 valid species, with many of them recognized as confirmed or potential vectors of important pathogens of animal health. The enriched species composition highlights the importance of systematic surveys in this island ecosystem and the need to determine the role of midges, if any, in pathogen transmission. Graphical Abstract